Une approche unifiee de Ia modelisation des structures complexes : les elements finis avec degre de Iiberte de rotation - lbrahimbegovi, Adnan; Frey, Francois; Rebora, Blaise (European Journal of Computational Mechanics, 1993)
In FE models of complex structural ~ystem.s, different element& need to be used such as: beams, membranes, solids, plates and shells. Elements of different kind, based on classical formulations, generally do not share the same nodal degrees of freedom, which complicate& construction of a compatible model. To resolve this modeling problem, we propose a family of finite elements ba.sed on a non-classical variational formulation of classical continuum, in which an independent rotation field is present. Along with a modified method of incompatible modes, this provides a unified basis for construction of variou.s finite elements with the same nodal degree11 of freedom, which can be freely combined. More specifically, new membrane, solid and triangular plate elements are given in the paper. The performance of presented elements is evaluated on a set of numerical examples, which include the numerical studies of the element junctions.